Th17-related cytokines and chemokines are associated with immune dysregulation and severity in schizophrenia - Liang, Han; Xu, Jing (Frontiers in Psychiatry, 2025)
BackgroundSchizophrenia is a complex neuropsychiatric disorder increasingly recognized as involving neuroimmune dysregulation. Among immune pathways, the Th17 axis and chemokine-mediated signaling have gained attention for their roles in chronic inflammation and neurotoxicity.ObjectivesThis study aimed to examine serum levels of Th17-related cytokines (IL-17, IL-21, IL-22, IL-23) and chemokines (CCL2, CCL5, CCL20, CXCL10, IL-8) in schizophrenia patients compared to healthy controls and to explore their associations with symptom severity and laboratory parameters.MethodsA total of 77 schizophrenia patients and 41 healthy controls were assessed. We used ELISA to find out how much cytokines and chemokines were in the serum. The Positive and Negative Syndrome Scale (PANSS) was used to rate how bad the symptoms were. We used Mann–Whitney U tests, Spearman correlations and principal component analysis (PCA) to look at the data.ResultsPatients had much greater levels of IL-17, IL-22, IL-8and CCL20 (p < 0.001), as well as higher levels of CXCL10 and CCL5 and lower levels of CCL2. IL-17, IL-21, IL-22and CCL2 all had positive relationships with the intensity of negative symptoms (N-PANSS). PCA showed that immunological markers grouped in different ways, with IL-21/IL-23 and IL-17/IL-8 being the most important inflammatory parts.ConclusionOur results suggest that Th17-related inflammation plays a key role in schizophrenia, especially when it comes to negative symptoms. Immune marker profiling may help us understand how diseases work and find subgroups that may be treated in a more tailored way.